PENENTUAN TINGKAT KESEJAHTERAAN ANAK MENGGUNAKAN ALGORITMA C 4.5 - Yuli Murdianingsih; Abdul Syukur; Moch Arief Soeleman (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Realization of child welfare is a right of every child and is the responsibility of all. Today the program services are sporadic, discontinue and responsiveness is a result of not optimal data management with social welfare problems is very large. Need a model system that can help make decisions quickly, precisely and accurately. In this research the basic needs of children based on four parameters: physical, intellectual, emotional, social and spiritual. C4.5 algorithm implementated in the m system’s model of children's basic needs level is done by calculating the entropy and the gain of the parameters of physical, intellectual, emotional and spiritual social iteratively in order to obtain a decision tree and rules used to model. Data analisys base on 149 datas as the training data and the testing data is 37. The accuracy of the model to look at the performance of the system using confusion matrix. Systems decision trees obtained the degree of basic needs of children, from the decision tree obtained seven rules that are used in view, values of accuracy obtained 94,59 % . C 4.5 algorithm can be used for classification of the level of a child's basic needs are met and not met.